Therapeutic effects of curcumin on constipation-predominant irritable bowel syndrome is associated with modulating gut microbiota and neurotransmitters - Tu, Xiaoting; Ren, Hongyan; Bu, Shurui (Frontiers in Microbiology, 2023)
Constipation-predominant irritable bowel syndrome (IBS-C) is a functional bowel disease that affects 10-20% of the population worldwide. Curcumin (CUR) is widely used in traditional Chinese medicine to treat IBS, but its mechanism of action needs further investigation. Considering the use of CUR in the treatment of IBS and the relationship between gut microbiota and neurotransmitters, we hypothesized that CUR could treat IBS by modulating gut microbiota and neurotransmitter levels. In this study, we used mosapride (MOS) as a positive control to evaluate the changes in gut microbiota in IBS-C rat models after treatment with CUR or MOS by analyzing 16S rDNA variation. In addition, we investigated whether CUR or MOS influenced serotonin (5-HT), substance P (SP), and vasoactive intestinal peptide (VIP) levels in the serum and colon of IBS-C rats. The results showed that CUR treatment could improve the symptoms of IBS and regulate the serum levels of 5 HT, SP and VIP. In addition, treatment with CUR changed the relative abundance of Blautia, Sutterella, Acetanaerobacterium and Ruminococcus2 in the gut microbiota. In conclusion, this study showed that the efficacy of CUR on IBS-C was possibly by modulating the microbiota and lowering the serum levels of HT, SP, and VIP.